Pelatihan Pembuatan Kudapan Kaya Nutrisi dan Probiotik Guna Mencegah Stunting Di Mojokerto - Dewi Perwito Sari; Asri Wido Mukti (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Stunting state is related to the nutritional status of children. The proportion of malnutrition status in Mojokerto district is 18%. Nutrition improvement efforts can be made to overcome and prevent stunting problems, one of which is nutrition improvement that is done in the First 1000 Days of Life of the children through complementary feeding. Therefore this Community Service aims to provide training in making complementary feeding which nutrients rich and probiotics. Pumpkin is used into pudding products that are rich in iron and lactobacillus. The method used is problem recognition, pre-socialization questionnaire filling, implementation of snack making training, interactive discussion, filling out post-socialization questionnaire and pudding product distribution of training results. The paired t-test analysis results from the questionnaire showed that there was an increase in knowledge, understanding of posyandu cadres about stunting prevention efforts through the provision of nutrient-rich snacks as well as the benefits of probiotics for health especially the digestive tract and its role in stunting prevention (p > 0.05).